Instrumento de referência e contrarreferência: percepção de profissionais da rede de atenção à saúde que atendem crianças/adolescentes com doença crônica - Santos, Maria Carolina Salustino dos (2021)
Children/adolescents with chronic illness regularly visit the health care facility and need an effective referral and counter-referral system to ensure continuity and integrality of care. Objective: It analyzes the reference and counter-reference instrument used in by health professionals healthcare system in a city of Paraiba caring for children/adolescents with chronic illness. Methodology: Qualitative, exploratory-descriptive research, carried out between June and October 2020 with 11 healthcare professionals at the primary, secondary and tertiary levels of the healthcare. The in-depth data collection took place remotely, and the Inductive Thematic Analysis interpreted the data. The project was approved by the Research Ethics Committee, under CAAE: 30673720.6.0000.5188 and Protocol No. 4,003,220. Results: Health professionals showed weaknesses in the structure and content of the reference / counter-reference instrument, which have not contributed to sharing information between services and have a negative impact on their work process in different levels of care. Also, the referral and counter-referral system’ regulation tool has not helped the healthcare professionals to monitor the children/adolescents through the healthcare system. With these deficits, the logistical system is damaged, making the healthcare system of children/adolescents with chronic disease unfeasible. It indicates the need to improve the referral and counter-referral system. Final considerations: The need to review the instrument was identified and establish through the flows and counterflows of information to organize the processes and improve the reference and counter-reference system. Thus, this care can be qualified by favoring the integration of health services for children and adolescents with chronic disease.